The Role of Volume Fraction and Additives on the Rheology of Suspensions of Micron Sized Iron Particles - Bossis, Georges; Volkova, Olga; Grasselli, Yan; Ciffreo, Alain (Frontiers in Materials, 2019)
The increase of the yield stress versus the magnetic field is the most important quantity characterizing the efficiency of a magnetorheological suspension. The theory based on the formation of columnar aggregates predicts a linear variation with the volume fraction of magnetic particles. We shall review previous models for the calculation of forces and yield stress and will introduce a new one based on rupture at zero strain. The predictions of these models are compared with the experimental data obtained for carbonyl iron particles by different authors. Whereas previous analytical prediction strongly overestimates experimental yield stress, the one calculated from Finite Element Method (FEM) used with affine trajectories well reproduce the experiments and show a linear dependence with the volume fraction and a H3/2 behavior between 50 and 200kA/m. Nevertheless, at very high volume fractions (>55%) where the suspension can only flow in the presence of specific additives, the dependence of the yield stress versus the volume fraction and the magnetic field is dramatically changed. We observe a jamming transition which is triggered by the application of a low magnetic field and which depends strongly of the volume fraction. We will discuss the new perspectives arising by the use of these very high volume fractions.